The Description of Religious-Enlightenment Themes in Mahmur’s Poetry (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article examines examples of Makhmour's poetry, touches on the thematic aspects of his literary heritage in general, and analyzes some of the poet's poems on religious and elevating themes.This study examines the religious-enlightenment themes in the poetry of Makhmour, emphasizing their significance in the poet’s literary heritage. While Makhmour is primarily known for his satirical compositions, his religious and social poetry provides valuable insights into the socio-political and spiritual atmosphere of his time. A review of existing literature highlights the central role of religion in state development and governance, reinforcing the poet’s critique of religious figures and institutions. The research addresses a knowledge gap regarding the integration of religious discourse within Makhmour’s poetic expressions, especially in relation to his critique of corrupt religious leaders.The study employs a qualitative literary analysis, examining primary sources such as Makhmour’s ghazals and satirical poems. The findings reveal that the poet utilized a blend of satire and religious reflection to expose societal injustices and advocate for ethical governance. His poetry portrays a critical yet nuanced perspective on the intersection of faith, power, and morality.The results indicate that Makhmour’s religious-enlightenment themes serve as both a critique of the ruling class and a reflection of the socio-religious consciousness of his era. This study contributes to the understanding of Uzbek literary traditions by illustrating how poetry functioned as a medium for social commentary. The implications of this research highlight the enduring relevance of Makhmour’s works in discussions on literature, religion, and governance.